Almost Tancred: Tasso's Sources, Rinaldo, and the Estensi as Crusaders. (31st December 2022) - Petrizzo, Francesca
Abstract: Torquato Tasso's Gerusalemme liberata (1581) has proven one of the most enduringly influential depictions of the First Crusade. This article aims to analyse it as a propaganda poem written in the service of the House of Este, Tasso's patrons, which celebrates their role in the fight against the Ottoman Empire, and projects a concept of Italian national identity consonant with the crusading movement. By examining the role played by Rinaldo in this poem, this article highlights how Tasso's sophisticated use of historical and literary references underpins a complex and sometimes contradictory ideological agenda in Liberata . The article demonstrates how Rinaldo was explicitly written as a stand-in for the Estense dynasty, and how the description of his fight against the Muslims was intended to idealise the House of Ferrara's hoped-for role as defeaters of the Turks. Furthermore, it is shown how Rinaldo was based on the historical Tancred as depicted by William of Tyre and Albert of Aachen, something which anchored the fictional character to historical "truth" in accordance with the ideals of the Counter-Reformation, and strengthened his propagandistic appeal. It is then demonstrated how the focus on "Italian crusaders, " achieved by centring much of the poem's action on Rinaldo and Tancredi (a fictionalisation of Tancred), inspired a trend of unpopular but historically significant poems on "Italian" crusaders across the peninsula. The article concludes by showing the contextual and ephemeral nature of this achievement, and how Tasso's revision of Liberata in the later (and quite unpopular) Gerusalemme conquistata completely left behind both Rinaldo and the ideological and political agenda of the original version.